Wild Edible Plant Diversity in Alpine Region of Himachal Pradesh - Panwar, Vijender Pal; Singh, Joginder; Rajasekaran, A.; prashad, Jawala; Kumar, Kuldesh (Indian Forester, 2023)
Study assessed the diversity of wild edible species in the alpine region of Kinnaur district, Himachal Pradesh, following the quadrat method and using random sampling. In total, sixty two plant species were recorded from the study area, Out of which shrubs and herb species were twelve and fifty, respectively. Among these, 29.03% of plant species were edible, and 70.97% were non-edible. Two were shrubs among the edible plants, and the remaining 16 were herbs. The density of edible shrubs Rosa webbiana (0.10 bushes/9m2) and Rhododendron campanulatum (0.08 bushes/9m2) was less as compared to non-edible species like Astragalus candolleanus (0.36 bushes/9m2) and Berberis jaeschkeana (0.31bushes/9m2). Syringa emodi, a non-edible shrub, was the dominant shrub species with an IVI value of 53.53. The total density of wild edible herbs was (2.60 individuals/m2)lower than the density of non-edible herb species (14.56 individuals/m2). Bistorta affinis, a rarely used herb had the highest density of 0.57 individuals/m2, frequency (12.21 %) and IVI (6.65) among edible herbs. Allium wallichii and Eremurus himiliacus were the most preferred edible species recorded from the study area. The people mainly visit the alpine region during the summer months with their domestic animals. As a result, knowledge of wild edible plant species is diminishing, especially among the younger generation. Therefore, public awareness and community-based management need to be encouraged to conserve plant species at all levels.